Relaciones Existentes Entre El Perfil Profesional, La Formacion Profesional Y El Campo Laboral De Los Estudiantes De Licenciatura En Educación Física Y Deportes De La Universidad De Quindio. (2015)
The present research is called "relationship between the social movement, professional profile and professional formation of students of degree in Physical Education and Sports of Universidad del Quindio", by the general objective, which pretended to understand these relationships and specifics objetives, where they were allowed to recognize, identify and describe this. The research approach was implemented a qualitative nature of type micro ethnography, people were students, teachers and graduates of degree of Physical Education and Sports of Universidad del Quindio, The depth interview like a collection technique. Based on the findings and the fact that inquired, you can answer the question about what relationships exist between professional formation, professional profile and social movement, where it was evident that these three aspects are interrelated in different ways, either among all as at starting point and at end point and a close relationship between two of the items. Plus there is evidence of a direct link between the diverse training in a field look for the preparation of the work and career and profile denoting the professional features that demarcate the joint work and in turn other relationship between the Country profile and Labour as joint training and intervention from the knowledge gained.